An exploratory evaluation of the pulpability of Brachystegia spiciformis and Pericopsis angolensis from the angolan miombo woodlands - Vicente Sangumbe, Lino Manuel; Pereira, Miguel; Carrillo, Isabel; Teixeira Mendonça, Regis (Maderas. Ciencia y Tecnología, 2018)
Brachystegia spiciformis and Pericopsis angolensis are two hardwood species found in the Miombo woodlands. The wood features, kraft pulping and strength pulp properties of both species were evaluated in order to determine their potential as raw material for papermaking. Brachystegia spiciformis wood density was 640 kg m-3 and Pericopsis angolensis was 795 kg m-3. Pericopsis angolensis wood has higher cell wall thickness and occluded fibre lumen as remarkable anatomical properties. Runkel ratio, slenderness ratio, and the coefficients of flexibility and rigidity in Brachystegia spiciformis were 1.5, 65.7, 41.2% and 29.4%, while in Pericopsis angolensis these values were 17.6, 59.9, 5.4% and 47.3%, respectively. Brachystegia spiciformis has a higher cellulose content, lower hemicellulose and lignin content, and higher S/G ratio than Pericopsis angolensis. In kraft pulping, a higher demand of active alkali was needed for both species, and pulps with high kappa number (24–27) and low pulp yield (40%) were obtained. Pericopsis angolensis pulps reached tensile, tear and burst indexes of 99.6 Nm g-1, 5.9 mN.m2 g-1 and 4.9 kPa.m2 g-1, respectively. Brachystegia spiciformis pulps reached tensile, tear and burst indexes of 100.3 Nm g-1, 10.7 mN.m2 g-1 and 6.1 kPa.m2 g-1, respectively. As a conclusion, Brachystegia spiciformis wood has better pulpability than Pericopsis angolensis wood, according to its pulps properties, despite of the similar pulp yield between both species. Both species may be suitable for unbleached wrapping papers and rigid cardboards manufacturing.